Retrospection and separation: Narratives of nostalgia among rural students in Chinese universities - Song, Longhua; Chen, Yufeng; Xu, Haoran (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
The phenomenon of rural-origin university students expressing nostalgia and sharing it through online platforms has become a growing behavior amid rapid globalization and urbanization. This study aims to explore the factors influencing this behavior and its impact on the social and psychological identity of these students. A total of 32 rural-origin university students were selected as informants for semi-structured interviews lasting between 20 and 50 minutes. The data collected were analyzed using Nvivo14 software through three stages of coding: open coding, principal axis coding, and selective coding. Using a grounded theory approach, this study analyzes five key factors influencing nostalgia behavior: emotional factors, real-life situations, interactive participation, technological support, and information diffusion mechanisms. The findings reveal that academic pressures intensify their sense of separation from rural life, and social challenges in the urban environment, intensify their longing for a simpler and more familiar way of life. Online platforms provide a space for students to express themselves, form virtual communities, and seek solidarity in shared experiences. Technology and anonymity enable freer expressions of nostalgia and its rapid dissemination, creating a collective narrative that strengthens their emotional bonds with their past. This study sheds light on the psychosocial challenges rural students faces in adapting to urban environments and the tension between rural traditions and the demands of urban life. Consequently, nostalgia serves not only as an emotional coping mechanism but also as a means for students to maintain their identity amidst the rapid social changes they encounter.